Studies on the thermal stabilization for Polyvinyl chloride by some metal stearates - A. Mahdi, Haider; Y. Kadhum, Mouayed; H. Anathiel, Amal (University of Thi-Qar Journal of Science, 2011)
In this study, preparation of some metal stearates derived from stearic acid with metals ;Iron , Cobalt, Nickel, Copper and Zinc . They were used as thermal stabilizers for Polyvinylchloride. These metal stearates were identified by elemental analysis and infraredspectroscopy.I.R, spectroscopy within the rang 1500-1900 cm-1 was used to study the thermalstability for PVC containing prepared metal stearates , and that depending on thin filmstechnique . The variations in the absorption bands intensity of the groups C = O , C = C ,COO - at 195oC were studied at different times (15 ,30 ,45 , 60 min) from thermal stress.These variations resulted from the rule of the metal stearates in the stabilizing of polymer .U.V-V.S spectroscopy was used to study the thermal degradation of unstabilized PVC andthe reprecipitated PVC from the stabilizers .This study was carried out by the investigation ofthe polymer resulted from the evolving of HCl from the polymer chain at 275nm and 385 nmcorresponding to three and seven conjugated double bonds respectively .The results wereindicated that metal stearates and their synergistic mixtures have the ability to stabilize PVCby decreasing the conjugated double bonds in the polymer .The thermal stability of the unstabilized PVC and PVC containing different metalstearates was investigation by thermogravimetric analysis (TGA). Many functions werecalculated such as the decomposition temperature , rate of decomposition ,activation energy,char content ,and percentage of HCl evolving from the polymer chain . The results indicatedthat metal stearates was increasing the thermal stability for PVC.